The dialectics of capital: learning from Gran Chaco - Ceddia, M. Graziano; Montani, Rodrigo; Mioni, Walter Fernando (Springer, 2022)
The critical impact of humans on the biosphere has led scientists to coin the term Anthropocene. The global environmental changes associated with it are happening under the aegis of capitalism. A transition towards sustainability requires a critical scrutiny of capitalism. The social–ecological system (SES) approach conceptualises the relationship between the socio-economic subsystem and the biosphere. However, in its various operationalisations it either treats the former as a black box or it fails to capture dynamic aspects. We address these limits and develop a Dialectical Socio-Ecological System (D-SES) framework, which combines process ecology with historical materialism, to describe the emergence and persistence of capitalist dynamics. We draw on data collected through fieldwork and desk research and deploy our framework to study capital-intensive agriculture in the Chaco Salteño, an important agricultural frontier in South America, obtaining some general insights. We open up the socio-economic subsystem and break it down into a lower-level material/economic sphere and an upper-level cultural/institutional sphere. Capitalist dynamics emerge out of the peculiar relationships occurring both within and between these spheres. This configuration shows the typical signs of autocatalysis. It attracts resources and capital to expand itself (centripetality). It becomes more complex and organised over time, fine-tuning production modes, cultures, and institutions (directionality). It is subject to the laws of competition and profit maximisation, which emerge independently from the individual actors and processes making up the system (autonomy). Finally, it engenders frictions, reflecting class antagonism between the direct producers and the appropriators of wealth. These frictions can become leverage points for a system’s transformation.